Does the Standardization Process Matter? A Study of Cost Effectiveness in Hospital Drug Formularies - Kwon, Seok-Woo (Management Science, 2008)
While research on the cost effectiveness of standardization to date has focused on the impact of different degrees of standardization, it has paid insufficient attention to the process an organization uses to formulate and implement standardized procedures. Drawing on the organizational decision-making literature and procedural fairness literature, this study identifies a number of key process features in standardization and argues that variations in these process features across organizations help account for the varying success of standardization in achieving cost effectiveness. Using hospital drug standardization for coronary artery and pneumonia cases to ground much of the argument, I analyzed inpatient discharge data from Florida, Illinois, New York, and Texas, combined with an original survey of 243 hospital pharmacy directors. The results indicated that an increasing degree of standardization was associated with cost effectiveness when the level of formal objectivity in creating the standardized procedure was high and when there was due process in resolving disputes about the standardized procedure. This finding broadly supports the argument that the cost effectiveness of standardization depends not just on the degree of standardization but also on the process by which the standardized procedures are created and implemented.